Vulnerability models of brick and wood structures considering empirical seismic damage observations. (December 2021) - Li, Si-Qi; Liu, Hong-Bo; Chen, Yong-Sheng
Abstract: To further explore the empirical seismic capacity of brick and wood (BW) structures and the vulnerability characteristics of the multiple seismic intensity regions, a vulnerability analysis was conducted based on historical observation data and a field survey of 154 typical destructive earthquakes occurring in 18 provinces (municipalities and autonomous regions) of China from 1990 to 2010. Based on the data collection, classification, and mathematical statistics of the empirical seismic damage of BW structures, a vulnerability probability matrix model based on 11, 520.403 × 10 4 m 2 and 48, 456 BW structures was obtained and established. Considering the statistical analysis of the empirical data by year, frequency, survey area, and number, empirical vulnerability models (matrix, point cloud, function, and curve) based on the evaluation of the Chinese seismic intensity scale (CSIS) were established by employing the vulnerability probability model, nonlinear regression theory, and numerical analysis method. The failure ratio (FR) and exceedance probability (EP) were employed as vulnerability assessment parameters, and nonlinear vulnerability demand comparison models considering empirical damage of BW in different years were established. In addition, the mean damage index (MDI) parameter matrix model was proposed to evaluate the overall vulnerability of regional BW. Combined with creating the empirical seismic damage investigation sample database, the evaluation and prediction models of BW vulnerability based on MDI were conducted, considering the overall investigation area.